Direct Democracy on Election Day: Ballot Measures as Measures of American Democracy - Donna Kesselman (Transatlantica)
Ballot Measures (or Propositions) are a form of Progressive Era direct democracy which has regained momentum in recent years. Re-energizing voters in the 38 U. S. states where they raise grassroots and often controversial “wedge issues”, they also have spill-over effects in other areas of politics and civil engagement. This introduction provides background information about their workings and an update on recent stakes in local political environments: it introduces in-depth studies published in this issue of Transatlantica.